2003
DOI: 10.1080/00014788.2003.9729646
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure interactions: accounting policy choice and voluntary disclosure effects on the cost of raising outside capital

Abstract: In this research we consider how disclosure of accounting policy interacts with subsequent choice over voluntary disclosure of a non-financial performance metric. We compare and contrast regimes. In the first, firms are free to choose between a conservative or an aggressive accounting policy before they decide whether to make additional voluntary disclosures. In the other regime, all firms either voluntarily or via mandation use the same accounting policy. We then investigate the cost of raising capital for fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 31 publications
7
83
0
1
Order By: Relevance
“…According to (Poshakwale & Courtis, 2005) higher information disclosure decreases the investors' ambiguities, thereby enabling them to obtain stable good results, which in turn enables the company to absorb long-term investments, since these investments seem better than short-term ones, which positively influences the firm's market price and supply capacity and therefore decreases, the cost of capital. This result is consistent with the results of (Zare et al, 2013;Articah & Clarkson, 2010;Kothari et al, 2009;Bertomeu et al, 2011;Gietzmann & Ireland, 2005;Gietzmann & Trombetta, 2003;Botosan, 1997). Thus, this result leads to the rejection of the second main null hypothesis in this study.…”
Section: Results Of Main Research Hypotheses Testsupporting
confidence: 82%
See 2 more Smart Citations
“…According to (Poshakwale & Courtis, 2005) higher information disclosure decreases the investors' ambiguities, thereby enabling them to obtain stable good results, which in turn enables the company to absorb long-term investments, since these investments seem better than short-term ones, which positively influences the firm's market price and supply capacity and therefore decreases, the cost of capital. This result is consistent with the results of (Zare et al, 2013;Articah & Clarkson, 2010;Kothari et al, 2009;Bertomeu et al, 2011;Gietzmann & Ireland, 2005;Gietzmann & Trombetta, 2003;Botosan, 1997). Thus, this result leads to the rejection of the second main null hypothesis in this study.…”
Section: Results Of Main Research Hypotheses Testsupporting
confidence: 82%
“…It is also supported by the results of (Khalifa & Ben Othman, 2015;Zare et al,. 2013;Lara et al, 2011;Gietzmann & Trombetta, 2003). Thus, this result leads to the rejection of the first main null hypothesis in this study.…”
Section: Results Of Main Research Hypotheses Testmentioning
confidence: 68%
See 1 more Smart Citation
“…Gietzmann and Trombetta (2003) claim accounting conservatism to be a substitute for voluntary disclosure. Hence, as the firms increase the extent of their voluntary disclosures, the cost of raising capital is alleviated since this cost depends on how much information is attained by the firms' potential investors.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The endogenous voluntary disclosure investigated by Gietzmann and Trombetta (2003). They found that firms communicate information about their condition voluntarily by disclosing high quality information and selection of accounting policies.…”
Section: Literature and Conceptual Frameworkmentioning
confidence: 99%